2011
DOI: 10.1161/circulationaha.110.008698
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Scavenging by Red Blood Cell Microparticles and Cell-Free Hemoglobin as a Mechanism for the Red Cell Storage Lesion

Abstract: Background Intravascular red cell hemolysis impairs NO-redox homeostasis, producing endothelial dysfunction, platelet activation and vasculopathy. Red blood cell storage under standard conditions results in reduced integrity of the erythrocyte membrane, with formation of exocytic microvesicles or “microparticles” and hemolysis, which we hypothesized could impair vascular function and contribute to the putative “storage lesion” of banked blood. Methods and Results We now find that storage of human red blood c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

33
575
4
10

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 515 publications
(628 citation statements)
references
References 67 publications
33
575
4
10
Order By: Relevance
“…This also occurs during administration of some hemoglobin-based oxygen carriers (34 -48). Transfusion of banked blood of more than 2 weeks of age may show similar effects in vivo due to release of hemoglobin as the red cells degrade (49,50).…”
Section: Hemoglobin (Hb)mentioning
confidence: 99%
See 2 more Smart Citations
“…This also occurs during administration of some hemoglobin-based oxygen carriers (34 -48). Transfusion of banked blood of more than 2 weeks of age may show similar effects in vivo due to release of hemoglobin as the red cells degrade (49,50).…”
Section: Hemoglobin (Hb)mentioning
confidence: 99%
“…In addition, we have simulated our own kinetics measurements of NO uptake by microparticles derived from aged red blood cells under aerobic conditions (50). Unlike phospholipid vesicles, these microparticles still have lipid raft proteins and other components characteristic of red cells in their membrane (56).…”
Section: Hemoglobin (Hb)mentioning
confidence: 99%
See 1 more Smart Citation
“…These antagonist experiments proved that free Hb was a contributor to the observed adverse effects. Additionally, animal studies focused on the acute hemodynamic effects of stored blood have suggested that NO donors could be a therapeutic option to limit transfusion-related and hemolysis-induced pulmonary and/or systemic hypertensive responses in mice, rats, and sheep www.perspectivesinmedicine.org (Yu et al 2008(Yu et al , 2009Donadee et al 2011;Baron et al 2012). One of these studies identified Hb and Hb-containing RBC membrane microparticles released in vitro before transfusion as an additional factor that may enhance the adverse posttransfusion effects (Donadee et al 2011).…”
Section: Transfusion Of Stored Bloodmentioning
confidence: 99%
“…Additionally, animal studies focused on the acute hemodynamic effects of stored blood have suggested that NO donors could be a therapeutic option to limit transfusion-related and hemolysis-induced pulmonary and/or systemic hypertensive responses in mice, rats, and sheep www.perspectivesinmedicine.org (Yu et al 2008(Yu et al , 2009Donadee et al 2011;Baron et al 2012). One of these studies identified Hb and Hb-containing RBC membrane microparticles released in vitro before transfusion as an additional factor that may enhance the adverse posttransfusion effects (Donadee et al 2011). Blood transfusion leading to stimulation of the heme breakdown pathway and accumulation of heme catabolites was associated with anti-inflammatory and immunosuppressive effects in multiple animal models, and such effects could contribute to the immunecompromised state of severely ill and massively transfused patients (Yazdanbakhsh et al 2011).…”
Section: Transfusion Of Stored Bloodmentioning
confidence: 99%